1999
DOI: 10.1021/jm990267c
|View full text |Cite
|
Sign up to set email alerts
|

Conceptually New Sulfone Analogues of the Hormone 1α,25-Dihydroxyvitamin D3:  Synthesis and Preliminary Biological Evaluation

Abstract: A conceptually new series of vitamin D(3)-like nonfluorinated and fluorinated 16-ene side chain tert-butyl sulfones 3-7 has been synthesized. Even though these novel C,D-ring side chain analogues of the hormone 1alpha,25-dihydroxyvitamin D(3) (1,1,25D(3)) lack a terminal OH group, thought previously to be essential for high biological activity, they are highly antiproliferative and, in several cases, transcriptionally active in vitro but desirably noncalcemic in vivo. The side chain sulfone group may be bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…The results shown in Fig. 5B are consistent with QW binding to VDR and increasing its transcriptional activity (29). QW as well as EB 1089 promotes induction of the VDR within 24 hours, which persists for up to 72 hours; this observation indicates that their actions are likely to be mediated through the VDR despite the differences in binding affinity.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The results shown in Fig. 5B are consistent with QW binding to VDR and increasing its transcriptional activity (29). QW as well as EB 1089 promotes induction of the VDR within 24 hours, which persists for up to 72 hours; this observation indicates that their actions are likely to be mediated through the VDR despite the differences in binding affinity.…”
Section: Resultssupporting
confidence: 78%
“…It has been reported that the newly synthesized hybrid analogue QW-1624F2-2 (QW; prepared by incorporating the calcium ablating 1-hydroxymethyl alteration along with the potentiating C, D ring 16-unsaturation, side chain 24,24-difluorination, and 26,27-homologation) has potent antiproliferative effects in a skin tumor models (26,27), indicating that growth inhibition may not require the 1-a and 25-dihydroxy groups (28). The side chain group may be binding to the nuclear VDR as a hydrogen-bond acceptor, in contrast to the hydrogen-bond donor function of the 25-OH group of natural 1,25(OH) 2 D 3 (29). The QW compound is f100 times less calcemic than 1,25-(OH) 2 D 3 when administered to rats at 1 Ag/kg and has the potential to block CYP24 expression.…”
Section: Introductionmentioning
confidence: 99%
“…These include sulfone [152] and sulfoximine [44] derivatives of 1,25(OH) 2 D. The 16,23-diene-25 sulfone analog (compound CTA018/MT2832) [123] is particularly interesting from a therapeutic standpoint as it exhibits a dual mechanism of action. It acts as a potent and low-calcemic inhibitor of CYP24A1, and in addition was shown to be a potent activator of VDRmediated transcription [123].…”
Section: Cyp24a1 Inhibitorsmentioning
confidence: 99%
“…), as exemplified in Fig. 33 [56,58,59]. Some of the resulting compounds, in particular the 22(S)-hydroxy-falecalcitriol, exhibit excellent selectivity, having very high activity on human carcinoma lines (HT-29) without any calcemic effect, as assessed in vivo on rats [56].…”
Section: Vitamin D 3 Metabolitesmentioning
confidence: 99%